Small business management : an entrepreneurial emphasis - Longenecker, Justin Gooderl, 1917-; Moore, Carlos W.; Petty, J. William (Cincinnati : South-Western College, 2000)
This book is divided into five parts: Entrepreneurial Opportunities; Developing the New Venture Business Plan; Small Business Marketing; Managing Small Business Operations; and Financial Management in the Entrepreneurial Firm.
Keywords: Management; Small business; Small business -- Management